Prevalence and Reinfection Rates of Schistosoma mansoni and Praziquantel Efficacy against the Parasite among Primary School Children in Sanja Town, Northwest Ethiopia - Eden Woldegerima; Abebe Genetu Bayih; Yalewayker Tegegne; Mulugeta Aemero; Ayalew Jejaw Zeleke (Journal of Parasitology Research)
Background. Schistosomiasis is among the most widespread chronic infections in the world. The magnitude of the infection may show variations across different areas with respect to time. Praziquantel is a first line drug of choice for the treatment of schistosomiasis although its low cure rate has been reported in different parts of the world. Thus, an assessment of the magnitude of the diseases, the efficacy of currently available drugs, and reinfection rates is crucial. Objective. Our principal objective is to determine the prevalence and reinfection rates of Schistosoma mansoni and to evaluate the efficacy of PZQ against Schistosoma mansoni. Method. A school-based cross-sectional study was conducted on Sanja Elementary Schools, Sanja town, northwest Ethiopia. Stool specimens were examined using Kato-Katz method. Schoolchildren who tested positive for intestinal schistosomiasis and fulfilled the inclusion criteria took part in the efficacy and reinfection study. Positive participants were treated with 40 mg/kg of Praziquantel. Cure and egg reduction rates were evaluated three weeks after treatment. The intensity of infection was determined following the WHO’s guideline. Moreover, the reinfection rate of those who were cured was evaluated after a six-month posttreatment period. Data were analyzed using SPSS version 20. Results. At baseline, 130 (35%) of the 372 schoolchildren were found infected with Schistosoma mansoni. Out of the 130 infected schoolchildren, 112 (86.2%) had moderate infection intensity. Among the S. mansoni positive schoolchildren, 80 were included as study participants for the evaluation of PZQ efficacy, based on the inclusion criteria established by WHO. The cure and egg reduction rates were found to be 90% (72/80) and 99.5%, respectively. Of the seventy-two schoolchildren considered for the determination of reinfection rate, after 6 months of posttreatment, 13.9% were found to be reinfected. Conclusion. The schoolchildren in the three primary schools of Sanja are at moderate risk of the infection caused by S. mansoni. Although the therapeutic potency of PZQ at 40 mg/kg was efficient against S. mansoni, a high rate of reinfection was reported in the study site, suggesting the need for integrated schistosomiasis control measures.